Using a New Measurement to Evaluate Pain Relief Among Cancer Inpatients with Clinically Significant Pain Based on a Nursing Information System: A Three-Year Hospital-Based Study - Wang, Wei-Yun; Chu, Chi-Ming; Sung, Chun-Sung; Ho, Shung-Tai; Wu, Yi-Syuan; Liang, Chun-Yu; Wang, Kwua-Yun (Pain medicine (Malden, Mass.), 2016)
Objective. Developing a new measurement index is the first step in evaluating pain relief outcomes. Although the percentage difference in pain intensity (%PID) is the most popular indicator, this indicator does not take into account the goal of pain relief. Therefore, the aims of this study were to develop a pain relief index (PRI) for outcome evaluation and to examine the index using demographic characteristics of cancer inpatients with clinically significant pain. Design. Retrospective cohort study. Setting. A national hospital. Subjects. All cancer inpatients. Methods. Pain intensity was assessed using a numerical rating scale, a faces pain scale or the Face, Legs, Activity, Cry, Consolability (FLACC) Behavioral Tool. Using a nursing information system, a pain score database containing data from 2011 through 2013 was analyzed. Results. Cancer patients representing 93,812 hospitalizations were considered in this study. We focused on cancer patients for whom the worst pain intensity (WPI) was ≥ 4 points. PRI values of −62.02% to −72.55% were observed in the WPI ≥ 7 and 4 ≤ WPI ≤ 6 groups. Significant (P < 0.05) effects on PRI values were observed among patients who were > 65 years old, those who were admitted to the medicine or gynecology and those who had a hospital stay > 30 days. Conclusion. This hospital-based study demonstrated that the PRI is an effective and valid measure for evaluating outcome data using an electronic nursing information system. We will further define the meaningful range of percentage difference in PRI from various perspectives.